If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + 5) + -6(3x + -5) = 11x + 3(2x + -7) Reorder the terms: 4(5 + 3x) + -6(3x + -5) = 11x + 3(2x + -7) (5 * 4 + 3x * 4) + -6(3x + -5) = 11x + 3(2x + -7) (20 + 12x) + -6(3x + -5) = 11x + 3(2x + -7) Reorder the terms: 20 + 12x + -6(-5 + 3x) = 11x + 3(2x + -7) 20 + 12x + (-5 * -6 + 3x * -6) = 11x + 3(2x + -7) 20 + 12x + (30 + -18x) = 11x + 3(2x + -7) Reorder the terms: 20 + 30 + 12x + -18x = 11x + 3(2x + -7) Combine like terms: 20 + 30 = 50 50 + 12x + -18x = 11x + 3(2x + -7) Combine like terms: 12x + -18x = -6x 50 + -6x = 11x + 3(2x + -7) Reorder the terms: 50 + -6x = 11x + 3(-7 + 2x) 50 + -6x = 11x + (-7 * 3 + 2x * 3) 50 + -6x = 11x + (-21 + 6x) Reorder the terms: 50 + -6x = -21 + 11x + 6x Combine like terms: 11x + 6x = 17x 50 + -6x = -21 + 17x Solving 50 + -6x = -21 + 17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17x' to each side of the equation. 50 + -6x + -17x = -21 + 17x + -17x Combine like terms: -6x + -17x = -23x 50 + -23x = -21 + 17x + -17x Combine like terms: 17x + -17x = 0 50 + -23x = -21 + 0 50 + -23x = -21 Add '-50' to each side of the equation. 50 + -50 + -23x = -21 + -50 Combine like terms: 50 + -50 = 0 0 + -23x = -21 + -50 -23x = -21 + -50 Combine like terms: -21 + -50 = -71 -23x = -71 Divide each side by '-23'. x = 3.086956522 Simplifying x = 3.086956522
| 10y+10=5y+20 | | 18=24-3w | | 4=2v-10 | | 16+2u=56 | | 0.4x+0.96=2.96 | | X^2=7/4 | | -17/5= | | 13f+8=19f-17f-3 | | 120-40/7-5=x | | 3b+4=b+19 | | 4e-8=19 | | 4x-9=3(x+5) | | 4a=8-5a | | 7-16m=-20m-17 | | 0.9-0.45= | | 5=17-4n | | 4y+3=6y+8 | | 83-v=274 | | 8.2x-57.4=-24.6 | | 10v+5v=25 | | 15n-25n+8n=18 | | 4g-13=3 | | 3(4z+9)=20-7z | | 24-c=2(3) | | 8y-5y=-27 | | -12n-12=-11n | | (-4v+3)(8v+6)=0 | | 9400=10 | | 9y-4y-14=48.80 | | 8.2x-53.4=-24.6 | | (t)=4t+3t^3+2t-7 | | -28-3n=8+6n |